The Structure of American Foreign Trade: A New View Examined - Ellsworth, P. T. (The Review of Economics and Statistics, 1954)
IN a recent paper, Domestic Production and Foreign Trade; the American Capital Position Re-Examined, 1 Professor Wassily Leontief utilizes materials drawn from his wellknown input-output studies to fill one of the more conspicuously empty economic boxes, namely: the actual structural basis of international trade. The general theoretical principle of comparative costs, long with us, indicates the advantage to be gained from a suitable allocation of productive resources in each of the countries engaged in trade. But we have had so little systematic knowledge of the productive structure of our own or of any other national economy that the application of such general theoretical principles to the analysis and explanation of actual foreign trade relationships has been practically out of the question. For practical conclusions, we have been forced back on common sense. Thus: